The right as political phenomenon: criticism of standard interpretation in the philosophy of right with regard to the connection between law and politics - Caviglia Marconi, Alessandro (2016)
This work reviews the concept of right, pointing out that it is completely autonomous frompolitics and moral. This concept has been formulated by juridical positivism and absorbed byneoconstitutionalism and the theory of juridical argumentation. Opposite to this vision of right,the concept of law introduced is characterized by the reflection and states that the idea that law isnot only connected with politics but also comes out from the politics itself. Consequently, progressmade in the current school of Frankfurt on the reflection about justice, politics and law will be used